LOGISTICAL SUPPORT OF ENTERPRISE OPERATIONS UNDER MARTIAL LAW: PROBLEMS AND WAYS OF OPTIMIZATION - ZAHORIANSKA, Olena; ZIABREV, Valentyn; KYSHCHYK, Darya (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the specifics of optimizing logistics routes for an enterprise under martial law conditions. The research is based on the case of a food industry company operating in central Ukraine, which faces logistical challenges due to security risks, infrastructure destruction, and supply instability. The work presents a comparative analysis of two alternative routes on both local (Vlasivka–Svitlovodsk) and regional (Vlasivka–Kropyvnytskyi) levels. A mathematical model for evaluating cost, delivery time, road surface condition, and transportation safety was used to identify optimal solutions. The results of the study indicate that under normal conditions, shorter and more cost-effective routes are preferable. However, in case of weight restrictions or force majeure factors, longer routes with better safety scores become essential. The article emphasizes the importance of dynamic route planning, integration of risk factors, and the application of digital tools for timely decision-making. The proposed approach can be applied by logistics departments of other industrial enterprises operating in high-risk environments.In addition to route optimization, the study highlights the need for flexibility and the ability to quickly respond to changing external factors. In wartime conditions, traditional logistics strategies must be rethought to accommodate fuel shortages, damaged infrastructure, and the threat of cargo loss due to hostile actions. The use of real-time analytics, scenario modeling, and cross-departmental cooperation proves crucial for maintaining business continuity. Furthermore, environmental aspects such as CO₂ emissions were also considered as part of sustainable logistics planning. The findings support the implementation of digital navigation systems and adaptive logistics strategies to increase resilience and minimize losses during crisis situations.The article also suggests that training logistics personnel to operate in emergency environments can significantly improve decision-making and efficiency. Additional emphasis is placed on cooperation with local authorities to ensure timely updates on route availability and safety. Overall, the research contributes to the development of integrated logistics models that combine economic, safety, and sustainability aspects. These insights are relevant for industrial enterprises seeking to build resilient supply chains in uncertain and high-risk conditions.
Keywords: logistics optimization; martial law; route planning; transportation costs; risk management; digital tools; food industry enterprise